2012
DOI: 10.1108/13598541211258609
|View full text |Cite
|
Sign up to set email alerts
|

Conducting content‐analysis based literature reviews in supply chain management

Abstract: Purpose -Inconsistent research output makes critical literature reviews crucial tools for assessing and developing the knowledge base within a research field. Literature reviews in the field of supply chain management (SCM) are often considerably less stringently presented than other empirical research. Replicability of the research and traceability of the arguments and conclusions call for more transparent and systematic procedures. The purpose of this paper is to elaborate on the importance of literature rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
776
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 925 publications
(860 citation statements)
references
References 60 publications
4
776
0
6
Order By: Relevance
“…Based on the idea of Mayring [60] and their analysis, they provide guidelines for conducting content analysis, which is in turn the foundation for the paper at hand. In the following, the authors discuss the four suggested stages in conducting content analysis based on Mayring [60], i.e., material collection, descriptive analysis, category selection, and material evaluation, but extend the process with the suggestions of Seuring & Gold [61]. The proposed stages by Mayring [60] ensure validity as well as reliability and have been conducted successfully by other researchers of the field for similar objectives [12,17,23,61].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the idea of Mayring [60] and their analysis, they provide guidelines for conducting content analysis, which is in turn the foundation for the paper at hand. In the following, the authors discuss the four suggested stages in conducting content analysis based on Mayring [60], i.e., material collection, descriptive analysis, category selection, and material evaluation, but extend the process with the suggestions of Seuring & Gold [61]. The proposed stages by Mayring [60] ensure validity as well as reliability and have been conducted successfully by other researchers of the field for similar objectives [12,17,23,61].…”
Section: Methodsmentioning
confidence: 99%
“…In the following, the authors discuss the four suggested stages in conducting content analysis based on Mayring [60], i.e., material collection, descriptive analysis, category selection, and material evaluation, but extend the process with the suggestions of Seuring & Gold [61]. The proposed stages by Mayring [60] ensure validity as well as reliability and have been conducted successfully by other researchers of the field for similar objectives [12,17,23,61]. Additionally, in terms of validity and reliability, the content analysis research can be enhanced with the involvement of one more researcher during data search and analysis [62].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is used to map primary studies on a particular topic (Dresch et al, 2015), to critically evaluate the literature and to consolidate the results of relevant studies (Seuring & Gold, 2012;Dresch et al, 2015).…”
Section: Methodsmentioning
confidence: 99%